Systematization of a Training Experience for In-service Teachers through the Use of an Action Research Component - Rodríguez-Sosa, Jorge (2019)
The systematization of a relevant experience such as the training of 21 in-service teachers with the use of an action-research component was aimed at documenting and writing what happened, as well as explaining the results achieved as a result of the intervention. The aim was to interpret the experience critically, to learn from it and improve future practice. The study used qualitative and quantitative analysis techniques. The results suggest that the component favored teachers to question their own beliefs about teaching and strengthen their abilities to make teaching problematic. They also suggest that these changes occur in training events that include spaces for reflection and discussion about beliefs and practices.